Basics of Infant Conventional Mechanical Ventilation: An Interactive Animated Teaching Module - Megan E. Aurora; Kristinna Kopek; Gary M. Weiner; Steven M. Donn (Association of American Medical Colleges, 2017)
Introduction While conventional mechanical ventilation is a common therapy in the neonatal intensive care unit (NICU), pediatric residents receive insufficient instruction. This stand-alone computer module provides an interactive method of learning basic infant pulmonary physiology and principles of mechanical ventilation. Methods This module runs offline and is compatible with a variety of operating systems. Participants complete a six-question, case-based pretest. The seven-section instructional module is self-paced, narrated, animated, and interactive. Learners can repeat each section as needed. At the conclusion of the module, participants complete the same six-question test and receive feedback. In total, the module requires 15-20 minutes to complete. Results The curriculum has been implemented at the beginning of the NICU rotation over a 2-year period within our pediatric residency program. Participants preferred this interactive module and had higher posttest scores when compared to a PowerPoint presentation. After 4 months, there was evidence of knowledge decay. Discussion The interactive module is enjoyable, effective, and convenient. It engages participants in active learning and allows them to control the time and pace of their instruction. We have implemented the curriculum within our residency program and believe it would be useful for a variety of NICU health care providers.